Une fenêtre ouverte sur l’URSS : le Spoutnik Digest durant la Guerre froide (1968-1988) - Beauchamp, David (Université de Montréal, 2021)
The fall of the Soviet Union in 1991 allowed the Cold War historiography to renew itself: social and cultural dimensions are acknowledged and the outlook on the cultural material emanating from USSR can be analyzed with more scientific objectivity and an appeased perspective. In 1967, a new magazine appeared in many Western cities: the Sputnik Digest. Its name referred both to the Soviet satellite that fascinated the world ten years earlier and the Reader’s Digest, the famous American magazine specialized in content aggregating, the most read and sold internationally at the time. The Sputnik Digest, published on a monthly basis, even though looking similar to its American counterpart at first sight, contained texts directly extracted from official Soviet newspapers in USSR. Without doubt a propaganda tool, like its American counterpart, the magazine however offered a fresh insight of the USSR during the Cold War: from the Sputnik Digest point of view, the Soviet Union was a peaceful country, culturally rich and a great place to live in. The magazine prioritized the valorisation of the USSR as opposed to criticizing the capitalist Western powers and the United States. From that standpoint it radically diverged from the aggressive ideological tone of the Reader’s Digest. This master’s thesis, through this new perspective, will study the Sputnik Digest as a historical and cultural object between the years 1968 and 1988. By looking both at its format and content, it will examine the origins of this monthly journal, its targeted readership and the most covered themes, revealing the message of Soviet peace and goodwill that the magazine tried to spread worldwide during the Cold War.
Keywords: Cold War; Communism; Communisme; Cultural history; Culture; Guerre froide; Histoire culturelle; History - Russian and Soviet / Histoire de la Russie - histoire soviétique (UMI : 0724); Magazine; Propaganda; Propagande; Reader's Digest (RD); Spoutnik Digest (SD); URSS; Union soviétique; United States; États-Unis